Faktor–Faktor Yang Berhubungan Dengan Produktivitas Kerja Pada Karyawan Pabrik Tahu - Cheni Arti Aprilia; Rara Marisdayana; Suroso Suroso (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Muhammadiyah Makassar, 2022)
The success of an enterprise is seen from its productivity. The productivity of the tofu factory in Tangkit Lama Village has decreased. From the work process, it shows that the part that causes work productivity is boiling, this is because during the boiling process using a large fire so that the work environment becomes hot, the hot environment causes fatigue so that it has an impact on work productivity. The purpose of the study was to find out the factors related to work productivity in tofu factory employees in Tangkit Lama Village. This research is a quantitative study with a cross sectional design. The study sample was 35 tofu factory. The research instruments are questionnaires and WBGT Heat Stress Meter. The data were analyzed univariately and bivariately using the chi-square test. From the results of the study, it is known that 37.1% of respondents have poor work productivity, 100% of respondents work in at-risk work environment, 40.0% of respondents experienced moderate work fatigue, 68.6% of respondents had moderate length of service. Bivariate results showed that there was a relationship between fatigue and work productivity (p<0.05) and there was no relationship between length of work and productivity work (p>0,05).